THE REPRESENTATION OF GENDER STEREOTYPE IN BOROSONâ€™S THE GIRL WITH GHOST EYES NOVEL (PANOPTICON: Journal of English Studies, 2022)
The study entitled â€œThe Representation of Gender Stereotype in Borosonâ€™s The Girl with Ghost Eyes Novelâ€ is aimed at describing how gender stereotype representation is portrayed in the novel and analyzing how it affects the main characterâ€™s resistances in order to develop her character. In analyzing the problems, a theory from Ridgeway (2000) about one of the elements of stereotype is the one that represents gender and from Foucault (2001) about power resistance are applied. The approach that the writer used in this study was a qualitative approach by analyzing the data in the form of dialogues and narrative text in the story. The study revealed that there are gender stereotype representations such as the main character is portrayed as weak, domestic, and dependent. As the result, it shows that the main character successfully breaks the stereotype by developing her character and skills.Keywords: Character, Gender, Gender Stereotype, Novel, Power Resistance.